Effect of bioagents on Fusarium oxysporum f. sp. cumini causing wilt of cumin (Cuminum cyminum) - NITIN CHAWLA,; S. GANGOPADHYAY,; B.R. DHAKA, (Seed Research, 2026)
Antagonistic potential of four bioagents viz. Trichoderma harzianum, T. viride, Pseudomonas fluorescens and Bacillus subtilis was tested against cumin (Cuminum cyminum L.) wilt pathogen Fusarium oxysporum f. sp. cumini under laboratory conditions. Out of four bioagents, maximum inhibition of mycelial growth of test pathogen was recorded against P. fluorescens followed by T. harzianum and T. viride. The population of F. oxysporum f. sp. cumini in soil was relatively lower when P. fluorescens treated seeds were shown as compared to rest of the three bioagents. The results showed that P. fluorescens was most effective in enhancing root, shoot length and dry weight of cumin plants particularly when used at 8 g/kg seed.